The Effect of 8 Weeks of Combined Training with Consuming Methadone on Plasma Fibrinogen & CRP on withdrawal Addiction Women - Motahhareh Borsalani; Mohsen Ghofrani; Mohammad Reza Batavani; Ali Seraj (Allameh Tabataba'i University Press, 2020)
Background: In addiction field, there is more attention on men than women, while women are more vulnerable to addiction. Because of the importance of women in the family foundation, we decided to investigate this subject. Purpose: This study aims at the effect of 8-weeks of combined training with methadone on cardiovascular inflammatory markers fibrinogen and CRP on addicted women. Method: This study accomplished as a semi-experimental research. 24 addicted women were randomly selected as samples from Zahedan Mohabbat addiction Camp that divided in two groups of methadone (N= 11) and methadone/ exercise (N= 13) by the same variables such as age, BMI, type and duration of drug withdrawal. The protocol of combined exercise was included of aerobic added to strength training; also methadone was taken according to the camp instructions, too. Blood sampling, pre and post 8 weeks exercise were directly collected from anterior veins of samples and the levels of plasma fibrinogen and CRP were measured in lab. To compares of the pre and post tests means for each group as well as both groups, paired and independent t-test via SPSS software version 24 were used, respectively. Statistical significant level was considered PResults: The results showed that CRP values in both groups decreased significantly (methadone: P<0.05, T=-2.21 and methadone/ exercise P<0.05, T=-2.63). Also, plasma fibrinogen values in both groups increased significantly (methadone: P<0.05, T=5.03 and methadone/ exercise: P<0.05, T=4.21). Also, there were no significant difference between post-test's levels of CRP and fibrinogen between methods (P>0.05). Conclusions: It has suggested that the method of methadone/ exercise might be used as such as methadone method by the same results on plasma fibrinogen levels and CRP for withdrawal addiction women.